2022
DOI: 10.3390/ijerph192315582
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction among Young Adult University Students during the COVID-19 Pandemic: The Role of Peritraumatic Distress, Attachment, and Alexithymia

Abstract: The literature focused on the effect of the COVID-19 pandemic on young adult university students’ mental health shows a significant increase in psychopathological symptoms and Internet Addiction (IA). The key role played by attachment and alexithymia has also been suggested, but no study has explored the possible dynamic relationship between these variables. We recruited a sample of n = 410 young adult university students online. We assessed the attachment to parents and peers (through IPPA), alexithymia (thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 143 publications
2
12
0
1
Order By: Relevance
“…As already highlighted, studies conducted in different stages of the COVID-19 pandemic have revealed a positive corelation between different distress symptoms (e.g., specific phobia, anxiety, depression, avoidance behaviors, and compulsive behaviors) and internet addiction in samples of university students (e.g., Karakose, 2022 ; Priego-Parra et al, 2020 ; Servidio et al, 2021 ). As a result, many scholars have suggested that internet addiction might be a coping strategy employed by those with existing psychopathological difficulties (Marzilli et al, 2022 ). The positive correlation between inferiority feelings and internet addiction found in the present study might also point to a similar mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As already highlighted, studies conducted in different stages of the COVID-19 pandemic have revealed a positive corelation between different distress symptoms (e.g., specific phobia, anxiety, depression, avoidance behaviors, and compulsive behaviors) and internet addiction in samples of university students (e.g., Karakose, 2022 ; Priego-Parra et al, 2020 ; Servidio et al, 2021 ). As a result, many scholars have suggested that internet addiction might be a coping strategy employed by those with existing psychopathological difficulties (Marzilli et al, 2022 ). The positive correlation between inferiority feelings and internet addiction found in the present study might also point to a similar mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…It appears to have escalated its prevalence and severity since the outbreak of the pandemic, largely due to the reasons related to the strict precautions implemented during the pandemic, such as increased social isolation and the need for easy information (Li et al, 2021;Masaeli & Farhadi, 2021;Sun et al, 2020). Given the comorbidity between internet addiction and other psychological problems, especially depression and anxiety (Li et al, 2019;Soulioti et al, 2018), the rise in the Internet addiction problem during the pandemic has become a topic of increased concern (Marzilli et al, 2022). Having had to abruptly adapt to a wide array of challenges related to the pandemic, such as online classes, online assessments, and isolation from peers, university students, including those in Turkey, were specifically susceptible to the pandemic's detrimental effects on psychosocial functioning (Cam et al, 2022;Fila-Witecka et al, 2022;Savage et al, 2020), and Internet addiction (Mota et al, 2021;Varer Akpinar et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority period for using the Internet is at midnight, and using the Internet for leisure is one of the significant predictors of Internet addiction. Marzilli et al (2022), who examined how the COVID-19 pandemic affected young adult university students' mental health, found that psychopathological symptoms and Internet addiction significantly increased (IA). Alexithymia and attachment have also been cited as playing important roles, although no study has looked into how these factors might interact dynamically.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The widespread availability of high-speed internet, coupled with the need to research, complete assignments, and stay connected with peers, contributes to the increased risk of developing problematic internet use among university students. 17 Research has indicated a potential link between internet addiction and obesity, with excessive time spent online leading to a sedentary lifestyle, decreased physical activity, and weight gain. For university students, the allure of the internet lead to irregular eating patterns and unhealthy food choices as they mindlessly snack while immersed in their devices.…”
Section: Introductionmentioning
confidence: 99%